1983
DOI: 10.1126/science.6844918
|View full text |Cite
|
Sign up to set email alerts
|

Heinz-Body Hemolytic Anemia from the Ingestion of Crude Oil: A Primary Toxic Effect in Marine Birds

Abstract: Hemolytic anemia developed in young herring gulls and Atlantic puffins given daily oral doses of a Prudhoe Bay crude oil. Anemia developed 4 to 5 days after the initiation of oil ingestion and was accompanied by Heinz-body formation and a strong regenerative response. The data evince a toxic effect on circulating red blood cells involving an oxidative biochemical mechanism and the first clear evidence of a primary mechanism of toxicity from the ingestion of crude oil by birds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(38 citation statements)
references
References 14 publications
4
34
0
Order By: Relevance
“…Similar results were obtained in rats treated with gasoline vapors [19], in rats treated with Nigerian Bonny light crude oil [1,2], in rats treated with cypermethrin [20] and in rats treated with Doxorubicin [21]. It was found that treating rats with crude oil was associated with anemia of the haemolytic type [18,22]. Also, gasoline 80 inhalation may cause anemia where there was a decrease in Hb content in treated rats.…”
Section: Discussionsupporting
confidence: 72%
“…Similar results were obtained in rats treated with gasoline vapors [19], in rats treated with Nigerian Bonny light crude oil [1,2], in rats treated with cypermethrin [20] and in rats treated with Doxorubicin [21]. It was found that treating rats with crude oil was associated with anemia of the haemolytic type [18,22]. Also, gasoline 80 inhalation may cause anemia where there was a decrease in Hb content in treated rats.…”
Section: Discussionsupporting
confidence: 72%
“…The majority of post-spill studies involve birds that have been subjected to cleaning and rehabilitation procedures in addition to oiling itself, and it can therefore be difficult to separate the effects due to the cleaning operations from those due to oil ingestion (Eppley & Rubega 1990, Anderson et al 1996, Sharp 1996. However, one primary toxic effect that occurs consistently as a result of crude oil ingestion in birds is haemolytic anaemia (Leighton et al 1983). As disturbance of red blood cell function can affect other tissues, many of the recorded physiological and behavioural effects on birds may be secondary responses to a primary dysfunction of erythrocytes (Leighton et al 1983).…”
Section: Introductionmentioning
confidence: 99%
“…However, one primary toxic effect that occurs consistently as a result of crude oil ingestion in birds is haemolytic anaemia (Leighton et al 1983). As disturbance of red blood cell function can affect other tissues, many of the recorded physiological and behavioural effects on birds may be secondary responses to a primary dysfunction of erythrocytes (Leighton et al 1983). Anaemia is relatively simple to detect in blood samples and thus provides a nondestructive means of detecting physiological effects of crude oil exposure in wild birds.…”
Section: Introductionmentioning
confidence: 99%
“…Hematological effects, specifically hemolytic anemia and oxidant damage to red blood cells (i.e., Heinz bodies), have been observed in birds that have ingested 10 ml/kg body weight of unweathered Prudhoe Bay crude oil [31]. This finding was not corroborated in our study, but this may be attributable to differences in the chemical composition of the weathered versus unweathered oil, quantity of oil ingested, or the route of ingestion (bolus injection vs. dietary consumption).…”
Section: Chronic and Reproductive Effectsmentioning
confidence: 99%